Pengaruh Kualitas Pelayanan dan Kualitas Produk terhadap Loyalitas Konsumen PT. Trimasindo Global Perkasa - Auliana Khairany; Husnayetti Husnayetti (ITB Ahmad Dahlan Jakarta, 2020)
The purpose of this research is to study and analyze the effect of service quality and product quality on consumer loyalty of PT. Trimasindo Global Perkasa South Jakarta. The design in this study uses a quantitative associative method to find out the relationship between the three variables. Based on the results of research analysis in the research obtained significant value 0.002<0.05, then reject Ho and Ha accepted. Real t value shows that the quality of service has a direct relationship with consumer loyalty significant value 0.002<0.05, then reject Ho and Ha accepted. Real t value shows that product quality has a relationship that is in line with consumer loyalty. Could it was concluded that F 30,745>4.01, then refused Ho and accepted Ha That is, there simultaneously influences between service quality variables and product quality on consumer loyalty.